Understanding farm trajectories and development pathways: Two decades of change in southern Mali. (October 2015) - Falconnier, Gatien N.; Descheemaeker, Katrien; Van Mourik, Thomas A.; Sanogo, Ousmane M.; Giller, Ken E.
Abstract: Institutional support for smallholders has been the motor for the expanding cotton production sector in southern Mali since the 1970s. Smallholder farms exhibit diverse resource endowments and little is known on how they benefit from and cope with changes in this institutional support. In this paper we explore farm trajectories during two decades (1994 to 2010) and their link with farm resource endowment and government support. We distinguished a favourable period for cotton production and an unfavourable period during which institutional support collapsed. A panel survey that monitored 30 farms in the Koutiala district in southern Mali over this period was analysed. Based on indicators of resource endowment and using Ascending Hierarchical Classification (AHC), farms were grouped into four types: High Resource Endowed farms with Large Herds (HRE-LH), High Resource Endowed (HRE) farms, Medium Resource Endowed (MRE) farms and Low Resource Endowed (LRE) farms. Average yield, labour productivity and food self-sufficiency status of each type were calculated. Farms remaining in the same type were classified as 'hanging in', while farms moving to a type of higher yields, labour productivity and food self-sufficiency status were classified as 'stepping up', and farms following the opposite trajectory of deteriorating farming conditions were classified as 'falling down'. The LRE farms differed from all other farm types due to lower yields, while both LRE and HRE farms differed from the MRE and HRE-LH farm types due to a combination of less labour productivity and less food self-sufficiency. During those two decades, 17% of the farms 'stepped up', while 70% of the farms remained 'hanging in', and only 13% of the farms 'fell down'. We found no obvious negative impact of the collapse of government support on farm trajectories. For MRE, HRE and HRE-LH farms, average N and P use intensity increased from 1994 to 2004 and then decreased during the following cotton crisis. On the other hand, organic fertilizer use intensity increased continuously over the entire monitoring period for HRE-LH and MRE farms. Crop yields did not change significantly over time for any farm type and labour productivity decreased. We discuss how technical options specific for different farm types (increase in farm equipment, sale of cereals, incorporation of legumes and intensification of milk production) and broader institutional change (improvement in finance system and infrastructure, tariffs) can enhance 'step up' trajectories for farming households and avoid stagnation ('hanging in') of the whole agricultural sector. Highlights: Farm trajectories were assessed during two decades (1994–2010) in southern Mali. 17% of the farms 'stepped up', 70% remained 'hanging in', and 13% 'fell down'. Cotton crisis (2004–2010) did not impact farm trajectories. Crop yields did not change significantly from 1994 to 2010. Fertilizer use intensity and labor productivity decreased during cotton crisis.